Enhancing the photo-electrocatalytic properties of g-C3N4 by boron doping and ZIF-8 hybridization - Atta, Mahmood Riyadh; Maizatul Shima, Shaharun; Khan, Maksudur Rahman Md; Bawadi, Abdullah; Al-Mahmodi, Akram Fadhl; Nur Diyan, Mohd Ridzuan; Munusamy, Thurga Devi; Jun Wei, Lim (Elsevier B.V., 2023)
Developing the ideal catalyst for photo-electrocatalysis applications is attracting wide interest. In this study, the photo-electrocatalytic properties of metal-free catalyst g-C3N4 modified with ZIF-8 and boron doping were investigated. Bulk g-C3N4 was synthesized by thermal decomposition of melamine; boron doping was performed via co-condensation, while the ZIF-8 hybridization was performed by in-situ heterogeneous deposition method. The physicochemical properties of the catalysts were characterized by X-ray diffraction analysis, Fourier-transform infrared spectroscopy, UV–VIS, X-ray photoelectron spectroscopy, field emission scanning electron microscopy and elemental mapping. The band gap energies increased from 1.878 eV for g-C3N4 to 2.36, 2.28 and 2.42 eV for B-g-C3N4, g-C3N4/ZIF-8 and B-g-C3N4/ZIF-8, respectively. Moreover, CO2 reduction in a PEC cell using the prepared catalysts as working electrodes was conducted to evaluate the photo-electrocatalytic properties using cyclic voltammetry, electrochemical impedance spectroscopy and linear sweep voltammetry. Incorporation of ZIF-8 significantly influenced the photocatalysis properties by increasing current density from a −1.08 mA/cm2 for g-C3N4 to a −1.52 mA/cm2 in g-C3N4/ZIF-8, and slightly increased the electrical conductivity from a −0.846 mA/cm2 to a −1.235 mA/cm2. In the other hand, boron doping only influenced the electrical properties of g-C3N4 where its reductive current increased from 0.065 mA (g-C3N4) to a 0.34 mA (B-g-C3N4) at −0.404 V potential voltage. As a result, merging these modifications noticeably enhanced the photo-electrocatalytic activity and light sensitivity of the main catalyst, which opens a wider range of applications and future research.